TAZKIYAH AS A PROPHETIC MISSION IN THE QUR'AN: A COMPARATIVE STUDY OF THE INTERPRETATION OF HAMKA AND HASBI ASH-SHIDDIEQY - Rega Agustian (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study examines the concept of tazkiyah (soul purification) as the main pillar of prophetic mission in the Qur'an through a comparative study of Nusantara exegesis. The focus is directed at the interpretation of two authoritative Indonesian mufassirs of the 20th century, Haji Abdul Malik Karim Amrullah (Hamka) in Tafsir Al-Azhar and Tengku Muhammad Hasbi Ash-Shiddieqy in Tafsir Al-Qur'anul Majid An-Nur. Through library research with a descriptive-analytical-comparative approach, this study analyzes five main verses containing the term yuzakkihim (purifying them), namely Surah Al-Baqarah (2): 129, 174; Ali 'Imran (3): 77, 164; and Al-Jumu'ah (62): 2. The analysis results show that Hamka reconstructs the meaning of tazkiyah in an integrative-holistic manner covering physical hygiene (physical-hygienic aspect) and spiritual purity (theological-moral aspect). Conversely, Hasbi Ash-Shiddieqy consistently interprets tazkiyah within the limits of spiritual purification, namely liberation of the soul from the stain of shirk, superstition, heresy, and formation of noble moral character for social order.